PENGARUH PENERAPAN METODE PEMBELAJARAN GAMIFICATION TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA TEKNIK OTOMOTIF - Gunawan, Dicky; Cahyasari Putra, Ricky; Deni Ramdani, Sulaeman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to analyze the effect of implementing gamification learning methods on the learning motivation and learning outcomes of Automotive Engineering students. The research was conducted on 11th-grade students of the Automotive Engineering major at SMKN 2 Kota Serang using a quantitative approach through a quasi-experimental design of the nonequivalent control group type. The research subjects consisted of two classes: the experimental class, which received gamification learning treatment, and the control class, which used conventional learning methods. The sampling technique was conducted using purposive sampling. Data on learning motivation were collected using questionnaires, while learning outcome data was obtained through cognitive domain learning outcome tests. The research instruments underwent validity and reliability tests, resulting in a Cronbach’s Alpha coefficient of 0.954, indicating very high reliability. Data analysis was conducted through descriptive and inferential analysis using prerequisite tests (normality and homogeneity tests) as well as t-tests to examine the research hypotheses. The results of the study show that the application of the gamification learning method has a significant effect on increasing motivation and learning outcomes of Automotive Engineering students. In addition, there is a significant difference in learning motivation and outcomes between students in the experimental class compared to the control class. These findings indicate that the gamification learning method is effective as an innovative learning strategy to enhance students’ motivation and learning outcomes in vocational education.